The Jwaneng underground project: an overview of numerical modelling as a design tool - Dunn, M.J.; Kebatsetse, L.Q.; Bushula, E.; Rekopanye, C. (Caving 2026: Proceedings of the Sixth International Conference on Block and Sublevel Caving, 2026)
The Debswana Diamond Company (DDC) Jwaneng mine in Botswana is a large open pit diamond operation extracting 3 kimberlite pipes and has been in production since 1982. Open pit operations will cease in 2036, and studies are being undertaken to transition the mine to an underground operation. The Jwaneng underground project (JUP) is complex as it needs to consider 3 kimberlite pipes and there are many challenges and complexities. The study is currently at a pre-feasibility level and considers a range of mining methods over the 3 kimberlite pipes and different mining phases. The Jwaneng mine is structurally complex, with many large geological structures and a variable rock mass of strengths ranging from weak kimberlites (~25 MPa) to very competent dolomites (>250 MPa). Initially, mining of kimberlite wedges (Phase 1) on the pit walls will occur from underground and will be done using blasthole open stoping (BHOS) and sublevel retreat (SLR). A transition from this unconfined environment to a confined underground environment occurs below the pit (Phase 2), with extraction using sublevel caving (SLC) and block caving (BC). DDC has made significant efforts to develop the geotechnical model (geology, structural, rock mass, and hydrogeology) and the stress field as key design inputs. Numerical modelling has been used to evaluate a range of mine designs and design variations, including SLR/SLC drive spacing, BC height, access and infrastructure stand-offs, zone of influence, etc. Both FLAC3D (finite volume) and Abaqus (finite element) software were used as part of the design process and to allow the project team to make key design decisions. Various sensitivities for a range of input parameters were researched to understand what the models are sensitive to and to identify uncertainty. Results from the numerical modelling will be presented and summarised.